Detection of Blastocystis Hominis by Method of Cultivation in The Feces of Orphanage Children in Pekanbaru, Riau Province, Indonesia - Esy Maryanti; Suri Dwi Lesmana; Wira Firja; Muhammad Devlin; Mislindawati Mislindawati; Forman Erwin Siagian (Faculty of Medicine, Universitas Diponegoro, 2023)
Background: Blastocystis hominis is an intestinal protozoan that can infect humans and animals. The distribution coverage is very wide and is transmitted through the fecal-oral route. The incidence of blastocystosis due to Blastocystis hominis is higher in developing countries because it is associated with poor hygiene practice, inadequate sanitation, close contact with pets domesticated animals and or contaminated food. Blastocystis hominis infection can cause clinical manifestations, from asymptomatic to chronic diarrhea, depending on the Blastocystis subtype and the patient's immune system. brief background of the topic and significance of the study.Objective: The aim of this study was to detect and determine the incidence of Blastocystis hominis infection in the feces of children at the Pekanbaru Orphanage using the culture method.Methods: The sample is the feces of children from nine orphanages in Pekanbaru. Detection of Blastocystis by the modified Jone's Medium culture method but using sheep's serumResults: A total of 95 children's stool samples were examined from 9 orphanages in Pekanbaru, it was found that 63 children (66.3%) were positive for Blastocystis hominis using the culture method, positive Blastocystis hominis was found more in boys (58.7%%) than girls, and based on age group, 6-12 years were found to be the age group with the most infection (84.1%). Generally, the source of drinking water in orphanages is refilled drinking water and all orphanages have cats as pets, and a few have chickens, birds, and goats as petsConclusion: High incidence of Blastocystis hominis can be detected in the feces of Pekanbaru orphanage children using the culture method.